Lens redox imbalance after urban air pollution exposure - Janezic, Natasha Stephanie (2019)
Particulate matter (PM) present in air pollution produces adverse effects on the eye. Oxidative stress has been suggested to play a key role in the toxic mechanism. Lens antioxidant system maintains the redox status of nearby ocular structures. The aim of the study was to evaluate the redox balance in mice lens after the exposure to urban air pollution. 8- week-old Balb/c male mice were exposed to urban air or filtered air (UA-group and FA-group, respectively) in exposure chambers located in highly populated area of Buenos Aires city (averagelevel of PM: 25.6 ± 0.8 μg/m3). The animals were exposed for 8 h/day, 5 days/week, up to 12 weeks (CICUAL-FFYB, CUDAP 50946/16). Superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GR) activity, levels of reduced and oxidized glutathione (GSH and GSSG) and protein oxidation (PO)were evaluated in lens lysates. After 1 and 2 weeks of exposure, UA-group presented no significant differences in all measurements compared to the FA-group, except for SOD activity that was increased after 1 week (107 %, p<0.05). After 4 weeks, an increase in GR activity was shown in UA-group (47 %, p<0.05). After 12 weeks, GPx activity was increased in UA group (63 %, p<0.05), meanwhile GR activity decreased (40%, p<0.05) as well as the GSH/GSSG index (62 %, p<0.05), compared to FA-group. PO increased in UA-group (113 %,p<0.05), and an inverse correlation was found between PO and GSH/GSSG index (r= -0.9114, p<0.001). GPx activity and GSH/GSSG index also presented an inverse correlation (r= -0.7421, p<0.001) in UA-group. These results suggest that urbanair pollution exposure alters the redox balance of the lens, which could affect the antioxidant defenses of nearby ocular structures. The correlation between the PO and GSH/GSSG index indicates that lens GSH pool could prevent the protein oxidation, which has been suggested as one of the triggers of cataracts.